1986
DOI: 10.1007/bf00314021
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of peripheral neuropathy and cerebellar ataxia in chronic alcoholics

Abstract: A total of 78 chronic alcoholics were examined neurologically as well as by electroneurography, myography and posturography. Clinical signs of peripheral neuropathy were detected in 45% of these patients, with electromyographic and neurographic abnormality in 67% and 55% respectively. Clinical signs of cerebellar ataxia were found in 33% of our patients, whereas posturographic measurements of increased sway were recorded in 69%. The posturographic characteristics of cerebellar anterior lobe atrophy were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…Yet, age was similar in the present study and the study conducted by Nicolas and co-workers and daily alcohol intake was even higher in the present study (270 g/d vs. 170-197 g/d). Furthermore, the prevalence of clinical parameters suggestive of cerebellar ataxia was 27 % as revealed by the ICARS, which is very similar to the prevalence rate of 33 % reported by Scholz et al (1986) [36]. The difference between radiological and clinical measurements of cerebellar atrophy is already known from previous CT and MR studies [9,19,37].…”
Section: ■ Dentate Nuclei Intensity Does Not Correlate With Cerebellasupporting
confidence: 81%
See 1 more Smart Citation
“…Yet, age was similar in the present study and the study conducted by Nicolas and co-workers and daily alcohol intake was even higher in the present study (270 g/d vs. 170-197 g/d). Furthermore, the prevalence of clinical parameters suggestive of cerebellar ataxia was 27 % as revealed by the ICARS, which is very similar to the prevalence rate of 33 % reported by Scholz et al (1986) [36]. The difference between radiological and clinical measurements of cerebellar atrophy is already known from previous CT and MR studies [9,19,37].…”
Section: ■ Dentate Nuclei Intensity Does Not Correlate With Cerebellasupporting
confidence: 81%
“…Likewise, autopsy studies revealed that loss of Purkinje cells and atrophy of white matter were most prominent in the central lobule and the anterior folia of the vermis [5,32,44]. Clinical signs of cerebellar ataxia can be detected in around 30 % of patients with chronic alcohol consumption [36], whereas postmortem morphometric analysis demonstrated vermal atrophy in 27-42 % of brains of alcoholics [21,42].…”
Section: Introductionmentioning
confidence: 98%
“…A stationary level biomechanics force platform (model OR6-5; Advanced Mechanical Technology, Inc., Newton, MA) was used to measure postural sway, the corrective movements associated with the maintenance of upright posture, an excellent measure of cerebellar functioning in the alcoholic patient (Scholz et al, 1986). The postural sway measure was expressed as the excursion area covered by a patient during a 10-sec period of standing on both feet with eyes closed.…”
Section: Neurocognitive Testsmentioning
confidence: 99%
“…The effects of lead (Bhattacharya et al, 1988Bhattacharya and Linz, 1991;Chia et al, 1994;Yokoyama et al, 1997), toluene (Yokoyama et al, 1991), n-hexane (Yokoyama et al, 1996), styrene monomer (Ledin et al, 1989;Moller et al, 1990), mixed solvents (Antti-Poika et al, 1989;Ledin et al, 1989;Moller et al, 1989), alcohol (Diener et al, 1984b;Scholz et al, 1986; Yokoyama et al, (1997) + − − − + + − Lead-exposed children Bhattacharya et al (1988Bhattacharya et al ( , 1990Bhattacharya et al ( , 1991Bhattacharya et al ( , 1993 a In addition, an increase in sway speed by polychlorinated biphenyls and trichloroethylene has been reported (Kilburn et al, 1994). b Dx, Dy, length of sway path in right-left and anterior-posterior directions, respectively; S, sway area.…”
Section: Application In Occupational Andmentioning
confidence: 98%